Comparative Economic Analysis of Cotton Cultivation in Adilabad and Nalgonda Districts of Telangana, India: Insights for Sustainable Farming Practices - Shwetha M N; I. Shakuntala Devi; T. Lavanya; A. Meena (Archives of Current Research International, 2024)
Aims: Cotton plays a significant role in livelihood of cotton farmers and unskilled workers who depends on cotton textile industry. Knowing the cotton crop’s profitability at the farmer level is therefore equally crucial. The following study is aimed at estimating and analysis the cost of cultivation of cotton crop in Adilabad and Nalgonda districts of Telangana and compare the cost structure of the selected districts. Methodology: The study is based on primary data that was gathered using a pretested schedule from a sample of 120 farmers, with 60 of them coming from each chosen district. Descriptive statistics, including averages, percentages and other basic statistical techniques, were utilized in the study. Various cost concepts and different farm income measures were also used to achieve the objectives of the study. Results: The study showed that cost of cultivation in Adilabad was Rs. 99,077.86 ha-1 which is more than Nalgonda district estimated at Rs. 93,884.78 ha-1 and net revenue generated by cultivation was also following the same trend which was Rs. 25,394.54 ha-1 in Adilabad and Rs. 18,521.97 ha-1 in Nalgonda district. It was also noticed that yield was reduced drastically during the survey period i.e., 2021-2022, because of unseasonal rainfall that damaged the cotton crop heavily. While the prices were almost doubled compared to previous year. Conclusion: It can be concluded from the study that the cost of cultivation of cotton is increasing because of inappropriate usage of the inputs like plant protection chemicals and fertilizers and cultivation become less remunerative for cultivators. It is necessary that extension system to take lead role in creating awareness about optimal utilization of the resources.